1987
DOI: 10.1007/bf01313890
|View full text |Cite
|
Sign up to set email alerts
|

Genome variation among varicella-zoster virus isolates derived from different individuals and from the same individuals

Abstract: We have used 12 restriction enzymes to analyse the DNA of 24 clinical isolates of VZV derived from 12 patients in order to compare isolates derived from different individuals and derived serially from the same individual. As reported previously, only a small proportion of the isolates differed with respect to the presence or absence of restriction sites. However, we found that the size of DNA fragments generated from all the isolates derived from different patients varied in any of four regions, one of which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Viral DNA from the E2490 strain was extracted and purified as previously described (11). Viral DNA from HSV-1, HSV-2, HCMV, and SCMV was extracted and purified from the infected cells according to a previously described procedure (11). Trigeminal ganglia from four healthy seropositive cynomolgus macaques were used as test samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral DNA from the E2490 strain was extracted and purified as previously described (11). Viral DNA from HSV-1, HSV-2, HCMV, and SCMV was extracted and purified from the infected cells according to a previously described procedure (11). Trigeminal ganglia from four healthy seropositive cynomolgus macaques were used as test samples.…”
Section: Methodsmentioning
confidence: 99%
“…A cloned 2.6-kb SalI-EcoRI fragment containing the US4, US5, and US6 genes from the SMHV strain (SMHV/pBV-DNA) was provided by Akio Yamada (National Institute of Infectious Diseases of Japan). Viral DNA from the E2490 strain was extracted and purified as previously described (11). Viral DNA from HSV-1, HSV-2, HCMV, and SCMV was extracted and purified from the infected cells according to a previously described procedure (11).…”
Section: Methodsmentioning
confidence: 99%
“…Although loss or gain of restriction sites has been reported (Hondo et al, 1987), the principal form of genomic heterogeneity is due to size variation of restriction endonuclease fragments at discrete locations in the genome. With the advent of restriction endonuclease maps (Ecker & Hyman, 1982;Straus et al, 1982Straus et al, , 1983Davison & Scott, 1983;Gilden et al, 1983;Mishra et al, 1984), these locations were shown to correspond to each of the reiterations (Straus et al, 1983;Hayakawa et al, 1986;Hondo et al, 1987;Kinoshita et al, 1988;. Size heterogeneity is due to variation in the numbers of repeated elements present in the reiterations.…”
Section: A J Davisonmentioning
confidence: 99%
“…In the Dumas strain, it contains only one complete and one partial copy of the reiterated element, and was shown to be a true reiteration by examination of other VZV strains . R4 and R5 appear not to code for protein, whereas the elements that make up the other three reiterations are multiples of three bp and are (Oakes et al, 1977;Richards et al, 1979;Ecker & Hyman, 1981 ;Zweerink et al, 1981;Straus et al, 1981Straus et al, , 1983Straus et al, , 1984Martin et al, 1982;Pichini et al, 1983;Vlazny & Hyman, 1985;Hayakawa et al, 1986;Hondo et al, 1987;Kinoshita et al, 1988;. Although loss or gain of restriction sites has been reported (Hondo et al, 1987), the principal form of genomic heterogeneity is due to size variation of restriction endonuclease fragments at discrete locations in the genome.…”
Section: A J Davisonmentioning
confidence: 99%
See 1 more Smart Citation